A joint approach for strategic bidding of a microgrid in energy and spinning reserve markets. Issue 1 (February 2020) - Ferruzzi, Gabriella; Graditi, Giorgio; Rossi, Federico
In the electricity market, short-term operation is organized in day-ahead and real-time stages. The two stages that are performed in different time intervals have reciprocal effects on each other. The paper shows the strategy of a microgrid that participates to both day-ahead energy and spinning reserve market. It is supposed that microgrid is managed by a prosumer, a decision maker who manages distributed energy sources, storage units, Information and Communication Technologies (ICT) elements, and loads involved in the grid. The strategy is formulated considering that all decisions about the amount of power to sell in both markets and the price links to the offer, must be taken contextually and at the same time, that is through a joint approach. In order to develop an optimal bidding strategy for energy markets, prosumer implements a nonlinear mixed integer optimization model: in this way, by aggregating and coordinating various distributed energy sources, including renewable energy sources, micro-turbines–electricity power plants, combined heat and power plants, heat production plants (boilers), and energy storage systems, prosumer is able to optimally allocate the capacities for energy and spinning reserve market and maximize its revenues from different markets. Moreover, it is considered that both generators and loads can take part in the reserve market. The demand participation happens through both shiftable and curtailable loads. Case studies based on microgrid with various distributed energy sources demonstrate the market behavior of the prosumer using the proposed bidding model.